Mitochondrial DNA sequence variation in Hippopotamus amphibius from Kruger National Park, Republic of South Africa. Issue 2 (18th July 2016) - Beckwitt, Richard; Barbagallo, Jessica; Breen, Nickolas; Hettinger, Julia; Liquori, Angelo; Sanchez, Cesar; Vieira, Nathalia; Barklow, William
Abstract : Populations of Hippopotamus amphibius have declined throughout Africa in recent years, and are expected to decline further. An understanding of the population genetics of individual populations of hippos is necessary for effective management. To that end, we sequenced a portion of the mitochondrial DNA (mtDNA) control region or D-loop from 37 H. amphibius, from six herds in the central region of Kruger National Park (KNP), Republic of South Africa. We amplified a 453 bp segment by PCR, and identified 21 polymorphic sites and seven haplotypes. All of these haplotypes are private alleles, not found in other populations of hippos from southern Africa. Overall nucleotide diversity (π) was 0.01739, and haplotype diversity (hd) was 0.8273, within the range observed in other parts of Africa. Mismatch analysis conformed more closely to a model of constant population size than either rapid demographic or spatial expansion. An analysis of molecular variance demonstrated no significant differentiation among herds, and Mantel tests showed no significant relationship between geographic and genetic distance among herds separated by up to 47 km (measured as Euclidean [ x, y ] distance) or 77 km (measured along rivers). Over this range, the population appears to be a single panmictic unit. A test of the hypothesis that calves are more likely to share a mtDNA haplotype with an adult female in the same herd than an adult female from a different herd was not significant.